PENERAPAN MEDIA PEMBELAJARAN SIPERMAN UNTUK MENINGKATKAN MINAT BACA PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS V DI SDN PANDEANLAMPER 01 SEMARANG - Risky Heppy Panggalih; Henry Januar Saputra; Dyah Rahayu Tunjungsari; Sukamto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effectiveness and influence of SIPERMAN learning media in increasing students' reading interest in class V science and science learning at SDN Pandeanlamper 01 Semarang. The background to this research is that 69.5% of class VB students at SDN Pandeanlamper 01 still have low interest in reading. The method in this research is quantitative. The subjects in this research were class VB students at SDN Pandeanlamper 01 Semarang. The research instruments used were interviews, documentation, questionnaires and tests. The research design used was One-Group Pretest-Posttest Design. The data analysis technique in this research is inferential statistics. The data results were analyzed using N.Gain and t test. The N.Gain results show a value of 0.65, in the